Patient safety issues and concerns in Bhutan’s healthcare system: a qualitative exploratory descriptive study - Pelzang, Rinchen (BMJ Open, 2018)
OBJECTIVES: To investigate what healthcare professionals perceived and experienced as key patient safety concerns in Bhutan’s healthcare system. DESIGN: Qualitative exploratory descriptive inquiry. SETTINGS: Three different levels of hospitals, a training institute and the Ministry of Health, Bhutan. PARTICIPANTS: In total, 140 healthcare professionals and managers. METHODS: Narrative data were collected via conversational in-depth interviews and Nominal Group Meetings. All data were subsequently analysed using thematic analysis strategies. RESULTS: The data revealed that medication errors, healthcare-associated infections, diagnostic errors, surgical errors and postoperative complications, laboratory/blood testing errors, falls, patient identification and communication errors were perceived as common patient safety concerns. Human and system factors were identified as contributing to these concerns. Instituting clinical governance, developing and improving the physical infrastructure of hospitals, providing necessary human resources, ensuring staff receive patient safety education and promoting ‘good’ communication and information systems were, in turn, all identified as processes and strategies critical to improving patient safety in the Bhutanese healthcare system. CONCLUSION: Patient safety concerns described by participants in this study were commensurate with those identified in other low and middle-income countries. In order to redress these concerns, the findings of this study suggest that in the Bhutanese context patient safety needs to be conceptualised and prioritised.